Correlation Analysis of Twig and Leaf Characteristics and Leaf Thermal Dissipation of Hippophae rhamnoides in the Riparian Zone of the Taohe River in Gansu Province, China - Qun Li; Min Ma; Yurui Tang; Tingting Zhao; Chengzhang Zhao; Bo Li (Plants)
Aims: The functional traits of twigs and leaves are closely related to the ability of plants to cope with heterogeneous environments. The analysis of the characteristics of twigs and leaves and leaf thermal dissipation in riparian plants is of great significance for exploring the light energy allocation and ecological adaptation strategies of plant leaves in heterogeneous habitats. However, there are few studies on the correlation between the twig–leaf characteristics of riparian plants and their heat dissipation in light heterogeneous environments. Methods: In this study, the riparian plant Hippophae rhamnoides in Taohe National Wetland Park was the research object. According to the differences in the canopy light environment of the H. rhamnoides population, three habitat gradients were set: I, the full sight zone; II, the moderate shade zone; and III, the canopy cover zone. We studied the relationship between the twig–leaf characteristics of H. rhamnoides and leaf thermal dissipation in a heterogeneous light environment. Important Findings: The results are as follows: from the full sight zone to the canopy cover zone, the population characteristics and the twig, leaf, and photosynthetic fluorescence physiological characteristics of H. rhamnoides demonstrated significant changes (p < 0.05). In the full sight zone, H. rhamnoides tended to have thick leaves with a smaller SLA on short and thick twigs, and the light energy absorbed by the leaves accounted for a higher proportion of thermal dissipation. In the moderate shade zone, H. rhamnoides tended to grow many thin leaves with high SLA on long and thick twigs, and the proportion of light energy absorbed by the leaves for heat dissipation was lower than that in the full sight zone. In the canopy cover zone, H. rhamnoides tended to grow a few large and thick leaves with a low SLA on slender and long twigs, and the proportion of light energy absorbed by the leaves for heat dissipation was the lowest. There was a significant correlation between the twig–leaf and leaf heat dissipation of H. rhamnoides in the three habitats (p < 0.05). The co-variation of plant branches and leaves and the timely adjustment of thermal dissipation in photoheterogeneous habitats reflect the phenotypic plasticity mechanism and self-protection strategy of riparian plants in adapting to heterogeneous environments.